Growers’ Adoption of USDA GAP, Other Harmonized GAP & Group Produce Audits: Drivers, Constraints, and Fostering Improved Implementation - Jelili Adegboyega Adebiyi; Leslie D. Bourquin (Journal of Food Protection)
The USDA, with produce sector stakeholders, developed voluntary fee-for-service food safety audit schemes- USDA GAP&GHP, USDA Harmonized GAP (HGAP), USDA HGAP Plus+, and USDA GroupGAP- to help growers verify compliance with Good Agricultural Practices (GAPs). Aligned with produce safety regulatory requirements and designed to vary in scope and complexity, the schemes aim to meet diverse grower and buyer needs. For unclear reasons, growers’ adoption of USDA GAP audit schemes remains low relative to private standards. So, using data from growers (n = 208 surveyed) and service providers (n = 55 surveyed, 7 interviewed), we explored factors influencing growers’ implementation of USDA GAP programs. Buyers’ requests and food safety requirements were key drivers of adoption. However, many growers cited a lack of buyers’ demand for USDA GAP schemes, a key barrier to broader adoption. Small- and medium-scale growers also face technical and financial challenges inhibiting adoption, which could be addressed by government, private sector, and nonprofit stakeholders. Implementing USDA GAPs must be profitable for small growers, highlighting the need to align adoption efforts with USDA’s broader strategy to connect them to profitable markets. Negative audit experiences and concerns about nonconformities escalating to the FDA deter adoption. Enhancing outreach, education, and trust through Cooperative Extension and regional networks is crucial for improved understanding, acceptance, and adoption of USDA GAP schemes. The findings call for coordinated multi-stakeholder efforts to address the economic, informational, and perceptual barriers through targeted, multipronged interventions.